STUDI PEDAGANG KAKI LIMA DI SEPANJANG JALAN PASAR RAYA KOTA PADANG - Desi, Hanifa; Rianto, Slamet; Juita, Erna (STKIP PGRI Sumbar, 2013)
This study aimed to obtain the data,process, analyse, and discuss data on street vendors along the highway market Padang town. The type of research is descriptive. Population in this study amounted 287 people that all street vendors, and the sample totaled 71 people. Instrument used in this study is a questionnaire or a questionnaire. The data analysis uses the percentage formula. The result of this study found : 1) the vendors agree with the location they occupy in the desert town along the highway with the percentage 42.25%. 2) the street vendors agree with increased environmental hygiene along city highways sword with a percentage of 45.07%. 3) the vendors agree with environmental safety conditions along along the desert highway town with percentage 42.25%. 4) the vendors agree with supervision order environment in desert town along the highway with the percentage 42.25%.